2022
DOI: 10.1093/pnasnexus/pgac163
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of multiple dimeric states of E-cadherin by adhesion activating antibodies revealed through Cryo-EM and X-ray crystallography

Abstract: E-cadherin adhesion is regulated at the cell surface, a process that can be replicated by activating antibodies. We use cryo-EM and X-ray crystallography to examine functional states of the cadherin adhesive dimer. This dimer is mediated by N-terminal beta strand-swapping involving Trp2, and forms via a different transient X-dimer intermediate. X-dimers are observed in cryo-EM along with monomers and strand-swap dimers, indicating that X-dimers form stable interactions. A novel EC4-mediated dimer was also obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Since residue D58 on the 19A11 heavy chain forms a salt bridge with K14 on Ecad, it is likely that 19A11 binding blocks X-dimer formation. In agreement with this suggestion, a recent cryogenic electron microscopy study shows that 19A11 selectively interacts with Ecad strand-swap dimers and does not bind to X-dimers (20). While blocking X-dimer formation could potentially prevent strand-swap dimer dissociation and thus strengthen adhesion, our data suggest that the force-induced dissociation of strand-swap dimers do not involve an X-dimer intermediate.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Since residue D58 on the 19A11 heavy chain forms a salt bridge with K14 on Ecad, it is likely that 19A11 binding blocks X-dimer formation. In agreement with this suggestion, a recent cryogenic electron microscopy study shows that 19A11 selectively interacts with Ecad strand-swap dimers and does not bind to X-dimers (20). While blocking X-dimer formation could potentially prevent strand-swap dimer dissociation and thus strengthen adhesion, our data suggest that the force-induced dissociation of strand-swap dimers do not involve an X-dimer intermediate.…”
Section: Discussionsupporting
confidence: 91%
“…Previous structural studies ( 19 ) show that similar to wild-type (WT) Ecad, the K14E mutant interacts via strand–swap dimerization. Recent size–exclusion chromatography studies have shown that similar concentrations of 19A11 bind to both K14E mutant and WT Ecad ( 20 ). However, 19A11 does not recognize denatured Ecad in Western blots ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, this X-dimer was identified through sit e-directed mutations in E-cad (18, 19). More recently, the X-dimer was finally observed in wild-type cadherins using cryo-electron microscopy (20).…”
mentioning
confidence: 99%